2003
DOI: 10.1103/physrevlett.90.073001
|View full text |Cite
|
Sign up to set email alerts
|

Raman Regime Energy Dependence of Alignment and Orientation of KrIi States Populated by Resonant Auger Effect

Abstract: The energy dependencies of alignment parameters A20 for KrII 4p(4)5p states after the Auger decay of the KrI 3d(9)np resonances were investigated theoretically and experimentally for the first time in the Raman regime with the bandwidth of the exciting radiation (deltaE(FWHM)=20 meV) smaller than the natural width of the resonances (Gamma approximately 80 meV). The observed energy dependence is due to the in-terference between the different resonance channels and the direct photoionization channel. A strong en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 22 publications
(58 reference statements)
3
40
0
Order By: Relevance
“…However, 'nakajima@iae.kyoto-u.ac.jp the interference is usually extremely weak, since two electrons must be involved for the direct nonresonant photoionization to occur and accordingly, the probability of such a process is usually much smaller than that of the core excitation followed by the RA process. Nevertheless, a signature of interference between these two processes in the Auger electron spectra has been reported in earlier studies [2][3][4][5], The evidence of such interference has been more clearly observed in the angleresolved Auger electron spectra [6,7]. The use of an intense x-ray field has opened an opportunity to study new aspects of RA processes [8][9][10][11].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, 'nakajima@iae.kyoto-u.ac.jp the interference is usually extremely weak, since two electrons must be involved for the direct nonresonant photoionization to occur and accordingly, the probability of such a process is usually much smaller than that of the core excitation followed by the RA process. Nevertheless, a signature of interference between these two processes in the Auger electron spectra has been reported in earlier studies [2][3][4][5], The evidence of such interference has been more clearly observed in the angleresolved Auger electron spectra [6,7]. The use of an intense x-ray field has opened an opportunity to study new aspects of RA processes [8][9][10][11].…”
Section: Introductionmentioning
confidence: 97%
“…[17] w ith a bichrom atic field to dem onstrate the efficient m anipulation o f population in the core-excited state. However, the direct nonresonant photoionization process, w hich is essential to see the interference effect [2][3][4][5][6][7], is not included in their model, and moreover, the em ployed x-ray pulse is w eak. In contrast, our model incorporates the direct nonresonant photoionization process and the em ployed x-ray pulse is intense enough to induce a strong interference effect [9 -1 2 ], w hich can be confirm ed by the appearance o f an asym m etric profile in the A uger electron spectra [11].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The present measurements differ from the former studies mainly in the fact that much higher statistics has been obtained, which allowed us to observe the fluorescence polarization while scanning the excitation energy across the resonance with both linearly and circularly polarized photon beams. A similar experiment, using linearly polarized photons and a narrower excitation region, was performed recently in order to study, for the resonant 3d-np excitation of Kr, the influence of close lying resonances on the polarization state of the photoion [33]. [30,31].…”
Section: Experimental Confirmation Of the Scaling Effectmentioning
confidence: 99%
“…Alignment and orientation of the residual ion are usually obtained from angular distribution or polarization analysis of fluorescence emitted by a subsequent relaxation of the ion [2,3,4]. On the other hand, fluorescence experiments only allow a partial wave analysis of the emitted photoelectron waves [5,6].…”
Section: Introductionmentioning
confidence: 99%